Effect of resistance exercise on roller-ski performance in top junior cross-country skiers - Welde, B.; Svebak, S. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Success in cross-country (X-C) skiing requires a high VO2max and an ability to work at high intensity levels before the occurrence of a net accumulation of lactate (i.e. a high lactate threshold). It also requires a skiing technique that enables economical use of energy. It has been shown recently that upper body power adds a substantial contribution to X-C skiing performance (Gaskill, Serfass & Rundell, 1999). Also, findings from ski-specific testing in the laboratory, by use of treadmill roller-skiing or upper body ergometry (Rundell & Bacharach, 1995; Wisløff & Helgerud, 1998), and from field studies of determinants of X-C skiing performance (Mahood et al.), suggest better prediction of success in X-C skiing by scores on upper body aerobic power than by scores on VO2max or lactate threshold during running tests. These findings have stimulated interest in effects of performance adaptations to resistance exercise in X-C skiers, and performance improvements of maximal resistance training in the laboratory have been reported (Hoff, Gran & Helgerud, 2002; Hoff, Helgerud & Wisløff, 1999). However, competitive X-C skiing requires repetitive, prolonged, dynamic and sub-maximal muscular contractions that use only a small percentage of maximal muscle power. The total energy contribution during a typical X-C ski race is derived primarily from aerobic sources: The mean and peak O2 uptake during a 6 km X-C ski race was found not to be higher than 84% and 94% relative to VO2max during skiing (Welde et al., 2003). From this perspective it could be hypothesized that a resistance exercise regimen with emphasis on muscular endurance could be more favorable for X-C skiers than a regimen based on maximal resistance exercise. Thus, the aim of this paper is to study effects of two distinct intensive resistance exercise programs that differ in their number of repetitions and, therefore, in the total duration of contractions, and to relate these effects to roller-ski test performance. Methods Thirty-seven top junior X-C skiers and biathletes, 19 females and 18 males, added 9 wk of 3-d·wk-1 resistance training to their standard endurance training regimen. Subjects were randomly allocated to either a 3·6 repetition maximum (RM) model or a 3·30 RM model. The subjects participated repeatedly in four tests including (1) five strength-testing exercises, (2) an all-out 20-min exercise test on a treadmill, (3) a double-poling test on roller-ski and (4) a free-technique time-trial roller-ski test in varied terrain (T-T). The subjects gave their informed written consent to participate in this study. The study was approved by The Regional Ethics Committee for Research. A two-factor ANOVA was used to evaluate possible changes during the training period and possible differences between the two strength training protocols for the tests mentioned above as well as for the anthropometrical data. A multiple regression backward elimination procedure was applied to determine the best predictors of the T-T performance. Results Muscle strength rose from the pretest to posttest for all subjects pooled. There were no statistically significant differences between the two groups in scores from any of the four tests. The multiple regression analysis for all subjects pooled showed that the gain-scores in the push-up performance test significantly predicted the T-T performance (ß = -0.54, P = 0.001), and this result was confirmed in the female subgroup examined separately (ß = -0.71, P = 0.001). For the men examined separately the multiple regression analysis showed that the 3·30 RM model (ß = -0.69, P = 0.004) significantly predicted improvements in the T-T performance. Discussion/Conclusion Our findings were supportive to a complex effect of maximal and endurance resistance training upon X-C skiing racing performance, as measured by a T-T test. Upper-body power, as measured by push-up performance, significantly predicted T-T performance. For the females, gain in strength appeared to be the most important factor, and the distinction between maximal vs. endurance resistance exercise was not significant. The male skiers, in contrast, seemed to gain more from endurance-type than from maximal resistance training. This gender difference may be a matter for further investigation.